The Singapore water story : sustainable development in an urban city state - Tortajada, Cecilia; Joshi, Yugal Kishore; Biswas, Asit K. (New York, NY : Routledge, 2013)
'This book describes the journey of Singapore's development and the fundamental role that water has had in shaping it. What makes this case so unique is that the quest for self-sufficiency in terms of water availability in a fast-changing urban context has been crucial to the way development policies and agendas have been planned throughout the years'--
Includes bibliographical references and index.
Keywords: Municipal water supply -- Singapore; Water-supply -- Singapore; Water resources development -- Singapore